Assessment of sensory and chemical parameters of tea sausage. (September 2019) - Brankovic Lazic, I; Lilic, S; Jovanovic, J; Raseta, M; Mrdovic, B; Trbovic, D; Nastasijevic, I
Abstract: In the former Yugoslavia, the production of tea sausage started just over half a century ago. This type of sausage is mostly industrially produced, which means the quality of this product is not standardised, but it is acceptable to the majority of the population. In this study, the sensory proprieties and chemical characteristics of tea sausage were examined. Two types of tea sausage were made, which differed depending on the percentage of different categories of pork meat, while the amount of beef meat, solid fat tissue and other ingredients were the same. The results obtained show the average scores for all tested sensory properties almost equal. Chemical results show that tea sausage-group 1 had higher protein content (27.96%) than tea sausage-group 2, which had 25.25 % protein in meat, while the content of collagen in meat protein was similar in the two sausage groups. Moisture in these sausages was less than 35%, while the values of other parameters were similar. This study demonstrated that different quantity and quality of pork meat could influence the sensory properties and chemical composition of tea sausage.